The Enterococcus faecalis FabT Transcription Factor Regulates Fatty Acid Biosynthesis in Response to Exogeneous Fatty Acids - Zou, Qi; Dong, Huijuan; Zhu, Lei; Cronan, John E. (Frontiers in Microbiology, 2022)
The phospholipid acyl chains of Enterococcus faecalis can be derived either by de novo synthesis or by incorporation of exogenous fatty acids through the fatty acid kinase complex (Fak)-phosphate acyltransferase (PlsX) pathway. Exogenous fatty acids suppress fatty acid synthesis through the transcriptional repressor FabT, the loss of which eliminated regulation of de novo fatty acid biosynthesis and resulted in decreased incorporation of exogenous unsaturated fatty acids. Purified FabT bound to the promoters of several fatty acid synthesis genes that contain a specific palindromic sequence and binding was enhanced by acylated derivatives of acyl carrier protein B (acyl-AcpB). The loss of the PlsX pathway blocked FabT-dependent transcriptional repression in the presence of oleic acid. Transcriptional repression was partially retained in a E. faecalis ∆acpB strain which showed decreased fatty acid biosynthesis in the presence of exogenous unsaturated fatty acids. The FabT-dependent activity remaining in the ∆acpB strain indicates that acylated derivatives of AcpA were weak enhancers of FabT binding although AcpA is believed to primarily function in de novo fatty acid synthesis.